Insoluble glucan synthesis by Streptococcus mutans serotype c strains. - Kuramitsu, H K (1983)
Both dextransucrase and mutansynthetase activities have been purified from the culture fluids of Streptococcus mutans GS-5 (serotype c). Although homogeneous dextransucrase preparations normally synthesize little insoluble glucan, essentially all of the glucan synthesized by this enzyme in the presence of 1.5 M (NH4)2SO4 was water insoluble. Linkage analysis of the insoluble glucans indicated that the presence of NH4+ increased the portion of alpha-1,3-glucose linkages relative to alpha-1,6-glucose units in the product. Chromatofocusing of aggregated glucosyltransferase fractions synthesizing predominantly insoluble glucan yielded primarily dextransucrase activity separable from relatively low levels of mutansynthetase activity. The latter enzyme was detected only in 18-h assays and synthesized primer-dependent insoluble glucan, which was decreased in the presence of NH4+. In the absence of primer dextran T10, the addition of dextransucrase also stimulated insoluble glucan synthesis by mutansynthetase. Dextransucrase and mutansynthetase appear to be distinct enzymes, since the latter possesses a higher molecular weight (155,000 compared to 140,000), a much lower isoelectric point, and did not cross-react with antibody directed against dextransucrase. These results are discussed relative to the mechanism of insoluble glucan synthesis by S. mutans serotype c strains.